Bioactivity of radiopaque 45S5 bioactive glass with progressive additions of Bi2O3: A dissolution study under static conditions - Clavijo-Mejía, G. A.; Michálek, M.; Youssef, L.; Kaňková, H.; Galusek, D.; Boccaccini, Aldo R. (Ceramics International, 2024)
The integration of bioactive glasses (BGs) into hard tissues in in-vivo models can be evaluated through X-ray radiographs. The image contrast plays an important role and should be enhanced to improve accurate minimal invasive diagnostics of the performance of BGs containing implants after surgery. The present work shows the effect of the progressive addition of Bi2O3 (up to 12.2 wt%) on the structure, thermal properties, radiopacity, and bioactivity of 45S5-like BG obtained by quenching of the melt prepared from oxide precursors. The BG chemical composition, phase composition, structure, chemical state, thermal properties, and radiopacity were respectively investigated by X-ray fluorescence (XRF), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), differential scanning calorimetry (DSC), and radiopacity analysis according to the ISO13116:2014 norm. The bioactivity of the glasses was monitored by immersing them in a simulated body fluid (SBF) under static conditions. The apatite formation ability and ion concentration in SBF after 3, 7, 14, and 21 days were investigated by XRD, scanning electron microscopy (SEM), inductively coupled plasma optical emission spectroscopy (ICP-OES), and ICP mass spectrometry (ICP-MS). All samples were found to be X-ray amorphous. Simultaneous formation of [BiO3] and [BiO6] units is noted in the BG. The glass radiopacity increased up to 1.8 and 4.2 times compared to the reference glasses without Bi2O3. Bi2O3 additions in the glass slow down the formation of apatite-like structures as a result of the network forming role of [BiO3] and [BiO6] units in the BG. Nevertheless, the BGs with the 12.2 wt % Bi2O3 still shows the ability to form apatite deposits after 7 days of immersion in simulated body fluid (SBF).
CRIS-Team Scopus Importer:2024-05-10
Keywords: Bioactive glass 45S5; Bioactivity; Bismuth oxide; Radiopacity